TERMINATION OF CONTRACT OF EMPLOYMENT; REASON(S) REQUIRED OR NOT? A REVIEW OF GHANA’S LABOUR STATUTES AND CASE LAWS (UCC Law Journal, 2024)
The laws which regulate employment relations have gone through various stages from the master-servant relationship in the medieval period to the current statutory implied provisions embedded in employment contracts.  In the current era of insatiable search for the rights and dignity of all persons across the world, the need to ensure decent work conditions has been of great interest. The right of workers to enjoy employment security is entrenched in the International Labour Organization (ILO) Convention on Termination of Employment (Convention 158) and Termination of Employment Recommendations in 1963. State parties to the ILO are required to incorporate such provisions in their national laws. The ILO Conventions and Recommendations on termination of employment contract require that employment contract should be terminated on a stated reason but not at the whim and caprices of the employer. Though Ghana has not yet ratified the ILO Convention 158, the passage of the Labour Act 2003, (Act 651) was guided by the provisions in the ILO Convention on Termination of Employment. Notwithstanding the safeguards provided in Ghana’s Labour Act to protect employees from arbitrary termination of employment, the judicial interpretations have maintained the view that an employer can terminate an employment contract without giving reasons. This interpretation placed the Ghanaian worker at the mercy of the employer. What is worse is that many negotiated collective agreements contain provisions for the termination of a contract of employment at will. A recent judicial interpretation has departed from the previous view that an employment contract can be terminated without reason, thereby giving a sigh of relief to the Ghanaian worker. This paper, through theoretical reviews, seeks to reinforce the judicial interpretation that there must necessarily be a reason for the termination of a contract of employment.